Pilot-scale biomass gasification system for hydrogen production from palm kernel shell (part A): steady-state simulation - Hussain, M. (Springer Science and Business Media Deutschland GmbH, 2021)
Hydrogen (H2) production via biomass gasification has demonstrated to be a viable method to obtain environmental-friendly fuel. In this paper, steady-state modeling of palm kernel shell (PKS) steam gasification pilot-plant is developed and validated using experimental data. The process optimization study for the gasification of PKS utilizing the coal bottom ash as a catalyst is conducted in the continuous advanced fluidized bed technology pilot-scale gasification plant to determine the optimum conditions to produce maximum H2 and syngas composition. The optimum conditions for maximum H2 and syngas composition are a temperature of 625 Â°C, PKS particle size of 1â2 mm, and coal bottom ash to PKS percentage of 7.5 . The optimum operating condition results are then validated in the pilot-scale gasification system. Steady-state simulation of the pilot scale biomass gasification plant is then developed using Aspen PlusÂ® and validated using the experimental data. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.